THE EFFECT OF SOCIAL MEDIA MARKETING ON PURCHASE DECISIONS THROUGH CONSUMER BUYING INTEREST AS AN INTERVENING VARIABLE CASE STUDY OF COFFEE SHOP KOPIKUNI MEDAN - Muammar Rifqi; Yossie Rossanty; Elfitra Desy Surya (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The culture of drinking coffee is not just thirst-quenching but can be a companion to daily activities such as gathering with friends, running a business, attending reunions, and so on. As a result, the culture of drinking coffee has become an integral part of our lifestyle, yet we continue to ignore the fact that it has caused the popularity of coffee consumption to skyrocket. This type of research uses a quantitative approach. This research was conducted at Kopikuni Medan. The sample of this research is 22 X 5 110 respondents. Test the validity and suitability of the model Loading Factor, Average Variance Extracted (AVE), and Composite Reliability. Data analysis techniques used the Structural Equation Modeling (SEM) method to test the hypotheses in this study. Purchase intention has a positive and significant effect on purchase decision Social media marketing has a positive and significant effect on purchase intention Social media marketing has a positive and significant effect on purchase decision Social media marketing has an effect on purchase decision through purchase intention. This study concludes that the variable of social media marketing that is the most significant in purchasing decisions are context and communication. Therefore, Kopikuni is advised to optimize the context and communication aspects of social media marketing by paying attention to the delivery of messages, message designs, and content posted via Kopikuni social media. Thus, Kopikuni can be remembered more by customers.